The autophagy gene Atg16l1 differentially regulates Treg and TH2 cells to control intestinal inflammation - Agnieszka M Kabat; Oliver J Harrison; Thomas Riffelmacher; Amin E Moghaddam; Claire F Pearson; Adam Laing; Lucie Abeler-Dörner; Simon P Forman; Richard K Grencis; Quentin Sattentau; Anna Katharina Simon; Johanna Pott; et al. (eLife, 2016)
A polymorphism in the autophagy gene Atg16l1 is associated with susceptibility to inflammatory bowel disease (IBD); however, it remains unclear how autophagy contributes to intestinal immune homeostasis. Here, we demonstrate that autophagy is essential for maintenance of balanced CD4+ T cell responses in the intestine. Selective deletion of Atg16l1 in T cells in mice resulted in spontaneous intestinal inflammation that was characterized by aberrant type 2 responses to dietary and microbiota antigens, and by a loss of Foxp3+ Treg cells. Specific ablation of Atg16l1 in Foxp3+ Treg cells in mice demonstrated that autophagy directly promotes their survival and metabolic adaptation in the intestine. Moreover, we also identify an unexpected role for autophagy in directly limiting mucosal TH2 cell expansion. These findings provide new insights into the reciprocal control of distinct intestinal TH cell responses by autophagy, with important implications for understanding and treatment of chronic inflammatory disorders.